A self-report assessment of appearance-related safety behaviours: Development and psychometric properties. Issue 6 (5th November 2022) - Patel, Tapan A.; Stewart, Rochelle A.; Summers, Berta J.; Wilver, Natalie L.; Cougle, Jesse R.
Abstract: Background: Individuals with appearance concerns may engage in maladaptive appearance-related safety behaviours aimed at checking, hiding or fixing perceived flaws in their appearance. Aims: This investigation examined the psychometric properties of a newly developed measure of appearance-related safety behaviours across three different studies. Method: The first two studies utilized exploratory and confirmatory factor analysis, respectively, to understand the factor structure of the measure. The final version of the Appearance-Related Safety Behavior Scale (ARSB) consisted of 13 items and two subscales related to behavioural avoidance and appearance maintenance. Results: Number of appearance-related safety behaviours was positively associated with body dysmorphic disorder symptomology and functional impairment, as well as social anxiety and eating disorder symptoms. The measure also demonstrated convergent validity with other appearance-related measures. Scores on the ARSB also predicted performance on an appearance-related behavioural task (time spent fixing appearance prior to having a picture taken). The third study found that scores on the ARSB were higher in a body dysmorphic disorder sample compared with healthy controls. Furthermore, change in scores on the ARSB was correlated with change in body dysmorphic disorder symptoms and impairment in a treatment study for body dysmorphic disorder. Conclusions: Clinical implications and potential uses of the measure as a clinical and research tool are discussed.